A Phase‐Changing Polymer Film for Broadband Smart Window Applications. Issue 16 (19th August 2020) - Xie, Yu; Guan, Fangyi; Li, Zhou; Meng, Yuan; Cheng, Jiang; Li, Lu; Pei, Qibing
Abstract : Front Cover : In article number 2000290 by Lu Li, Qibing Pei, and co‐workers, a new smart window material is introduced for wide‐bandwidth optical modulation. Its opacity is switched based on differential change of refractive indices in a phase separated copolymer. The solid‐state copolymer film is opaque at ambient temperature and turns transparent above 46 °C, with solar transmittance modulation of 70% and infrared transmittance modulation of 80%.